Short segment myelitis as a first manifestation of neuromyelitis optica spectrum disorders. (March 2017) - Huh, So-Young; Kim, Su-Hyun; Hyun, Jae-Won; Jeong, In Hye; Park, Min Su; Lee, Sang-Hyun; Kim, Ho Jin
Background: Some patients with neuromyelitis optica spectrum disorders (NMOSD) present with spinal cord lesions extending fewer than three vertebral segments (short transverse myelitis, STM), hindering an early diagnosis. Objective: We investigated the frequency and imaging characteristics of STM lesions in patients presenting with myelitis as an initial manifestation of NMOSD. Methods: Patients seen at three referral hospitals in Korea between June 2005 and March 2015 who met the following inclusion criteria were recruited for review: seropositivity for aquaporin-4 antibody, initial presentation with myelitis and spinal cord magnetic resonance imaging (MRI) performed within 1 month of initial myelitis onset. Results: Of the 76 enrolled patients, 65 (85.5%) collectively had 69 longitudinally extensive transverse myelitis lesions, while the remaining 11 (14.5%) had a total of 15 STM lesions. Of the 15 STM lesions, 5 spanned 2.5 vertebral segments, 6 were continuous over two segments, 3 showed a length of 1.5 segments and 1 was confined to a single segment. On axial imaging, all of the STM lesions involved the central grey matter. Conclusion: These MRI findings suggested that STM does not preclude the possibility of an NMOSD diagnosis.